Spełnianie kryteriów optymalnego obszaru walutowego w kontekście powstawania szoków asymetrycznych na wybranych przykładach krajów członkowskich "piętnastki" - Czaja, Jarosław (Fulfilling the criteria of optimal currency area (OCA) within the context of arising of asymmetric shocks on chosen examples of EU 15 (so called: Old Fifthteen), 2006)
The purpose of the article is an analysis of OCA criteria taking into account the problem of asymmetric shocks, which arise in the countries of the euro area. The main question the author wants to find the answer is which old EU member states can manage asymmetric shocks without cost of adjustment, especially while it appears, that common currency has not been still the source of economic development. Additionally, the economic situation of the euro area members does not look optimistic comparing to Great Britain, which does not seem to resign from its own currency. The accession of new countries to the European Union and in the future to the euro area makes the proposed analysis of fulfilling the OCA criteria within the context of asymmetric shocks more reasonable.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 61-72